2012
DOI: 10.1016/j.joa.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The use of serum bepridil concentration as a safe rhythm control strategy in patients with atrial tachyarrhythmias

Abstract: a b s t r a c tThe aim of this study was to evaluate the clinical significance of serum bepridil (Bep) concentration (SBC) for safely managing patients with atrial tachyarrhythmias (AT). Methods and results: SBC was measured in 37 patients with AT, including atrial fribrillation (AF) (31 cases), AF þ atrial flutter (AFL) (4 cases), AFL (1 case), and atrial tachycardia (1 case). The patients were administrated Bep for more than 4 weeks at the same dose. SBC was positively correlated with Bep dose per kilogram o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A meta-analysis revealed that QT prolongation is associated with cardiovascular and sudden death [ 22 ], suggesting that patients with HF should be carefully monitored. Several studies reported that plasma bepridil concentration correlates with the daily dose [ 5 , 14 ], and this phenomenon is consistent with the findings of the present study (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A meta-analysis revealed that QT prolongation is associated with cardiovascular and sudden death [ 22 ], suggesting that patients with HF should be carefully monitored. Several studies reported that plasma bepridil concentration correlates with the daily dose [ 5 , 14 ], and this phenomenon is consistent with the findings of the present study (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The following patients were excluded from the analysis as follows: (1) patients with no plasma bepridil measurement, (2) patients without echocardiography data, (3) patients undergoing hemodialysis, and (4) missing data. In this study, patients who had been administered bepridil for at least 28 days beyond the steady state were selected for analysis as previously reported [ 14 ]. Blood samples were stored at 4 °C until measurement.…”
Section: Methodsmentioning
confidence: 99%
“…35 In another study, bepridil was administrated at a dose of 100 mg/kg for managing atrial arrhythmias, indicating that it has a very low level of cellular toxicity. 36 Moreover, a previous study showed that bepridil can increase the pH of acidic endosomes. 37 Administration of a high dose of bepridil is expected to have dual functions to slow down the virus replication in host cells by both inhibiting M Pro and raising the pH of endosomes.…”
Section: Resultsmentioning
confidence: 99%
“…28, 29 Bepridil increases the risk of polymorphic ventricular tachycardia (torsades de pointes), and a relationship between increased bepridil concentration and QT prolongation has been documented. 30- 34 The therapeutic range of bepridil is 250 to 800 ng/mL, and the risk of QT prolongation increases at plasma bepridil concentrations of >800 ng/mL. 33 The clearance of bepridil is low in low-body-weight individuals and elderly individuals.…”
Section: Commentarymentioning
confidence: 99%